OCHRONA DANYCH OSOBOWYCH W IRLANDII - Marcinkowski, Bartosz (Zeszyty Prawnicze, 2017)
Personal Data Protection in Ireland Summary The article is a short review of the personal data protection system in the Republic of Ireland. The review is made in the light of the Polish Data Protection Act of 1997 and Directive 95/46/EC (sections I and II). The introductory parts (sections I and II) include general remarks on the increasing importance and value of privacy and personal data. This increase results, among other things, from rapid development of the Internet and modern data processing and mining measures. Subsequently, in section III, the author discusses the constitutional environment of privacy and personal data protection rules in Ireland, as well as the role of court precedents and Directive 95/46/EC in this respect. Next part of the article (section IV) is dedicated to practical data protection issues identified and discussed by Irish authors, including specific exposures as well as differences between definitions in the Irish Data Protection Acts 1988-2003 and the UK Data Protection Act 1998, and influence of the latter (UK) Act on the Irish Data Protection Commissionaire’s decisionmaking process. Further comments (section V) focus on Data Protection Commissionaire’s rights and obligations (including in particular comments on the Data Protection Commissionaire’s free and friendly consultancy policy). The conclusion (section VI) briefly and synthetically summarizes similarities and differences between Irish and Polish personal data protection rules and practices, stressing issues requiring the European-wide common approach (e.g. in the fields of basic definitions or CCTV legal issues). Finally, the author observes that Polish authors’ reflections on personal data protection and the Polish practice are not inferior to the Irish ones even though Irish regulations have been in place for 10 years longer than the Polish ones.